The Role of South African Youth in Politics - Gila, Mandisa; Latief, Iman (Afrika Tanulmányok / Hungarian Journal of African Studies, 2019)
The Republic of South Africa is 25 years into its democracy and the youth of the country find themselves inextricably linked with the country’s politics. With a fastgrowing population, rapid urbanisation, gross overpopulation, inequalities as well as other issues faced by most developing countries, the youth of South Africa find themselves in the position of being the product of their history as well as the catalysts for their future.